Diabetes and Periodontitis - Role in Cognitive Impairment - Shikha Sharma; Ashita S Uppoor; Srikant Natarajan (Wolters Kluwer Medknow Publications, 2018)
>Introduction: The global burden of dementia, diabetes, and periodontitis is rapidly increasing and is becoming a serious area of concern. The incidence of diabetes and periodontitis usually increases in middle age, and because they share a bidirectional relationship, they are known to worsen if not controlled. Evidence suggests that the people who have diabetes are at a significant risk of developing dementia and in the last two decades, periodontitis has been increasingly linked with dementia. Currently, there is no definitive treatment of dementia.The Hypothesis: The patients who have uncontrolled diabetes with moderate-to-severe periodontal disease may be at a greater risk for developing neurodegeneration associated with dementia.Evaluation of the Hypothesis: The chronic effects of both periodontitis and diabetes may have an uncontrollable additive effect on the body of an aging individual. Immunosenescence may add to the complexity of such effects and in such a scenario, the complete resolution of the systemic inflammation or other interrelated process responsible for directly or indirectly triggering neurodegeneration may be compromised. We have proposed various interrelated mechanisms linking diabetes and periodontitis that may be amplified in an aging individual. These mechanisms may contribute to the neurodegeneration associated with dementia. Oral cavity is a major unbarred window into the systemic environment of an individual. Treatment and maintenance therapy for periodontitis on a routine basis may help reduce a significant amount of inflammatory load, especially in the diabetic population, who are at a greater risk for the future development of dementia.